Simulation of two-dimensional currents to the depth and suspended sediment concentration in Aceh Besar Waters. (May 2019) - Setiawan, I; Yuni, S M; Purnawan, S; Ilhamsyah, Y; Wafdan, R
Abstract: Aceh Besar Waters are geographically located at 5.3° - 5.7°N and 95.1° - 95.6°E which border Indian Ocean, Andaman Sea, and Malacca Strait in the West, North, and East, respectively. The purpose of this study was to simulate the circulation of current and suspended sediment transport driven by southwest and northeast monsoon. Model discretization cover 0.5 x 0.5 arcminutes (925 x 925 m) of spatial resolution with time interval of 9 seconds. The parameters of the model are wind friction Cd = 1.285x10 −3, bottom friction r = 0.0025, lateral eddy viscosity = 2500 m 2 /s. The primary data of estuary suspended sediment concentrations were collected in the coastal waters of Lhok Nga, Ulee Lheue, Lampulo, Alue Naga and Krueng Raya as input for the suspended sediment distribution model. The results of the study show that during southwest monsoon, the current in the western part of Aceh Besar Waters move northward and during northeast monsoon in the western and eastern part of the region, the current move toward south and west. Thus, the distribution of suspended sediments follows the direction of the current, where sediment concentrations are reduced when they are away from the coast.